Nekaj dilem glede koncepta krovnosti pri slovenskih zamejskih organizacijah - Valentinčič, Dejan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
Slovenian national minorities in the four Slovenia's neighboring countries are represented as a whole by the so-called umbrella organizations. Such status is recognized to these organizations by the countries where these communities live, as well as by the Republic of Slovenia. But among members of these Slovenian communities there are also very critical views that umbrella organizations do not have the necessary legitimacy and that such a system is not appropriate. The article first summarizes the historical reasons why the existing organizations established themselves as umbrella organizations, and then we present and compare the views of selected interviewees who are critical about the legitimacy and effectiveness of such an arrangement. We conclude with a reflection on possible reforms of representation of Slovenian minorities.
Keywords: democratic election; demokratična izvolitev; legitimacy (political science); legitimnost (politične vede); manjšinsko predstavništvo; minority representation; Slovene minorities; zamejski Slovenci